(Collins primary focus) comprehension pupil book 2 - Fidge, Louis (Collins Educational London, 2011)
Collins Primary Focus: Grammar and Punctuation Pupil Book 2 is aimed at ages 8+. Presented in a clear and colourful format, each grammar concept is supported by visual cues. Follow-up activities allow children to develop grammar and punctuation skills at different levels. Progress units provide opportunities for assessment and consolidation.Concepts reappear in each level to build confidence, reinforce learning and add complexityDemonstrates clear links between grammar and punctuationSupports all ability levels with a progression through solid practice of the core concept to using grammar and punctuation in the context of more extended writingEngages all children with an updated design and a range of exciting, new artwork